Enhancing Employee Performance in Islamic Banking: The Moderating Role of Religiosity - Yasir, Yasir; Bachmid, Sofyan; Ermawati, Ermawati; Noval, Noval; Nurwanita, Nurwanita (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
Organizational culture, happiness at work, and leadership have been widely studied, yet the complex interactions among these factors and the role of religiosity in employee performance remain poorly understood, especially in the context of Islamic banking. This study investigates these relationships and their impact on the employee performance of Bank Muamalat Indonesia (BMI) in the Palu Branch, with religiosity as the moderating variable. Data were collected using closed questionnaires from all employees at the branch and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that organizational culture and happiness at work significantly enhance employee performance, while leadership does not have a significant impact. Notably, religiosity strengthens the positive effect of organizational culture on employee performance, indicating that religious values can deepen employee commitment and productivity by providing greater meaning and purpose in their work. The study highlights the importance of incorporating religiosity to foster an inclusive and productive work environment in Islamic banking. Future research with a more comprehensive design and a more diverse sample is recommended to further explore these relationships.========================================================================================================ABSTRAK – Meningkatkan Kinerja Karyawan Perbankan Syariah: Peran Moderasi Religiositas. Meskipun budaya organisasi, kebahagiaan di tempat kerja, dan kepemimpinan telah banyak diteliti, kompleksitas hubungan di antara faktor-faktor tersebut dan peran religiositas terhadap kinerja karyawan masih belum terpahami dengan baik, terutama dalam konteks perbankan syariah. Penelitian ini bertujuan untuk mengkaji hubungan tersebut dan pengaruhnya terhadap kinerja karyawan Bank Muamalat Indonesia (BMI) Cabang Palu dengan religiositas sebagai variabel moderasi. Data penelitian dikumpulkan melalui penyebaran kuesioner kepada seluruh karyawan BMI di cabang tersebut yang kemudian dianalisis dengan Partial Least Squares Structural Equation Modeling (PLS-SEM). Hasil kajian menunjukkan bahwa budaya organisasi dan kebahagiaan di tempat kerja secara signifikan meningkatkan kinerja karyawan, sementara kepemimpinan tidak berpengaruh signifikan. Menariknya, religiositas memperkuat dampak positif budaya organisasi terhadap kinerja karyawan yang mengindikasikan bahwa nilai-nilai keagamaan dapat memperdalam komitmen dan produktivitas karyawan dengan memberikan makna dan tujuan yang lebih besar dalam pekerjaan mereka. Studi ini menekankan pentingnya integrasi aspek religiositas untuk membangun lingkungan kerja yang inklusif dan produktif di perbankan syariah. Penelitian lanjutan dengan desain yang lebih komprehensif dan sampel yang lebih beragam masih diperlukan untuk memvalidasi dan memperluas hubungan ini.